Sectorial policy of agriculture 2019-2024 Salvador - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The Salvadorian agricultural sectorial plan 2019-2014 elaborated with the support from CCAFS integrates strategic axes on climate change and gender.